Multi-Component Sequential Synthesis of Dihydroorotic Acid-Based Amphiphilic Molecules - Sani, Monica; Bellucci, Maria Cristina; Volonterio, Alessandro (Synthesis, 2022)
An efficient multicomponent sequential process, which occurs in mild condition has been exploited for the synthesis of systematically modified amphiphilic molecules where the cationic head is tethered to a lipophilic tail through a dihydroorotic acid linker. The process is operatively simple, high yielding, and flexible. Such a strategy could impact combinatorial synthesis of wide libraries of amphiphilic molecules to be tested as transfection agents and/or as antimicrobials.
Keywords: multicomponent reactions; domino process; amphiphilic molecules; cationic lipids; antibacterial